Liver-Mediated Adaptive Immune Tolerance - Zheng, Meijuan; Tian, Zhigang (Frontiers in Immunology, 2019)
The liver is an immunologically tolerant organ that is uniquely equipped to limit hypersensitivity to food-derived antigens and bacterial products through the portal vein and can feasibly accept liver allografts. The adaptive immune response is a major branch of the immune system that induces organ/tissue-localized and systematic responses against pathogens and tumors while promoting self-tolerance. Persistent infection of the liver with a virus or other pathogen typically results in tolerance, which is a key feature of the liver. The liver's immunosuppressive microenvironment means that hepatic adaptive immune cells become readily tolerogenic, promoting the death of effector cells and the “education” of regulatory cells. The above mechanisms may result in the clonal deletion, exhaustion, or inhibition of peripheral T cells, which are key players in the adaptive immune response. These tolerance mechanisms are believed to be responsible for almost all liver diseases. However, optimal protective adaptive immune responses may be achieved through checkpoint immunotherapy and the modulation of hepatic innate immune cells in the host. In this review, we focus on the mechanisms involved in hepatic adaptive immune tolerance, the liver diseases caused thereby, and the therapeutic strategies needed to overcome this tolerance.